2005
DOI: 10.1111/j.1551-2916.2005.00245.x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Synthesis Temperature on the Defect Structure of Boron Carbide: Experimental and Modeling Studies

Abstract: Boron carbide (B4C) was synthesized from the elements at temperatures ranging from 1300° to 2100°C using the spark plasma synthesis method. Significant densification commenced at about 1500°C and was accompanied by a corresponding decrease in the defect structure of this carbide. Changes in the X‐ray diffraction patterns were in agreement with predictions of simulation studies based on the presence of twins. Transmission electron microscopy observations were consistent with the experimental observations and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
40
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 84 publications
(43 citation statements)
references
References 18 publications
3
40
0
Order By: Relevance
“…This result is consistent with previous works in literature. 5,[31][32][33] According to our results, fine-grained specimens can be prepared from initial powders with an average size equal to 500 nm, provided that temperatures as high as 1700 • C with at least 5G between the sintering powder and the punches. Such temperature is significantly lower than those considered in previous works.…”
Section: Resultsmentioning
confidence: 98%
“…This result is consistent with previous works in literature. 5,[31][32][33] According to our results, fine-grained specimens can be prepared from initial powders with an average size equal to 500 nm, provided that temperatures as high as 1700 • C with at least 5G between the sintering powder and the punches. Such temperature is significantly lower than those considered in previous works.…”
Section: Resultsmentioning
confidence: 98%
“…). The XRD patterns for all boron carbide powders contained peaks that are present in boron carbides containing a high concentration of planar defects . B 3 C, B 4.3 C, and B 5 C powders contained residual carbon as indicated by the strong peak at 26.4° 2‐θ, which is associated with 2‐H graphite.…”
Section: Resultsmentioning
confidence: 99%
“…This suggested that some reduction had occurred during the sintering process. Anselmi‐Tamburini et al observed that existed twins are eliminated during sintering process with increased temperatures . Nevertheless, the dense RCR samples contain much higher twin density compared to the dense commercial samples.…”
Section: Resultsmentioning
confidence: 99%